#TITLE_ALTERNATIVE# - TAHA MAULANA (NIM 12205062); Pembimbing: Ir. Nenny M. Saptadji, Ph.D., DIMAS
Scaling is a common problem that occurs in geothermal wells, particularly wells dominance of water as occurs in several wells in Mount salak awibengkok studied in this thesis. Scale formed on the installation of a geothermal well production can cause a decrease in production wells, it can even lead to cessation of production. Therefore, prevention and handling of scaling issues is very important to be attention. Scale can be formed due to the chemical reaction by mixing a geothermal fluid with other geothermal fluid is different compositions, or also can be caused by changes in fluid properties due to changes in pressure and temperature cause changes in saturation of the substances making up the geothermal fluid. Substances making up the geothermal fluid will experience a change in saturation due to reactions that occur in the process of evaporation. The point of particular pressure and temperature conditions where the geothermal fluid evaporation is taking place, or start a phase change from one phase into two phases, commonly referred to as Flash Point. In these conditions the substances in excess of its saturation point will have precipitation. By knowing the location of the depth of the steam point or flash point, the geothermal fluid can be estimated where the scaling is the first time this has happened. The location of the depth of the flash point can be determined by calculating the pressure drop from the well head to the bottom of the well to achieve the conditions of fluid saturation temperature, that is the temperature where the flow is taking place in two phases. For example, there are Beggs & Brill method, Horrison-freeston method, and the Lockhart-Martinelli method. At this time studies used correlation is the correlation Beggs & Brill, which in previous studies considered the most valid.